Penetration of Flurbiprofen from a Locally Applied Sore Throat Lozenge and Spray into Cadaveric Human Pharynx Tissue: A Novel ex vivo Model and Microautoradiography Method - Turner R; Wevrett SR; Edmunds S; Brown MB; Kulasekaran A; Adegoke O; Farrah J (Dove Medical Press, 2021)
Rob Turner,1 Sean Robert Wevrett,1 Suzanne Edmunds,1 Marc Brown,1 Anuradha Kulasekaran,2 Oluwajoba Adegoke,2 John Farrah2 1MedPharm Ltd, Guildford, UK; 2Reckitt Benckiser Healthcare International Ltd., Slough, Berkshire, UKCorrespondence: Oluwajoba AdegokeReckitt Benckiser Healthcare International Ltd, Slough, Berkshire, UKTel +44 1482 582134Email joba.adegoke@rb.comObjective: Flurbiprofen 8.75 mg lozenge and spray are used for symptomatic relief of sore throat, with a rapid onset of analgesia suggesting a localized mechanism of action. Building on previous studies, this investigation aimed to use microautoradiography to visualize the depth penetration of radiolabeled flurbiprofen into human pharynx tissue using an ex vivo model. Quantification of flurbiprofen in the tissue was performed to provide a quantitative representation of flurbiprofen distribution through the tissue.Methods: Cadaveric human pharynx tissue was mounted between the donor and receiver compartments of a Franz diffusion cell. After that 8.75 mg spray and dissolved lozenge formulations, containing radiolabeled flurbiprofen, were added to the donor compartment of a Franz diffusion cell. After incubation for one hour, the pharynx tissue was removed, processed, and sectioned both horizontally and vertically. The sections were placed within an imaging cassette to determine the penetration of radiolabeled flurbiprofen visually, before being solubilized to quantify the amount of flurbiprofen present in each section.Results: In the horizontally sectioned samples, flurbiprofen was present in the top layers of all replicates and decreased in intensity throughout the tissue. Of the applied dose, 48.0– 99.9% of flurbiprofen was detected in the top one-third of the pharynx tissue, closest to the dosing site, and 0– 14.8% of flurbiprofen was detected within the deepest third of pharynx tissue, furthest from the dosing site. In the vertically sectioned tissue samples, radiolabeled flurbiprofen was found at a high intensity at the dosing site and reduced in intensity throughout the thickness of the tissue. Lateral penetration of flurbiprofen was also seen in tissue dosed with the spray.Conclusion: Our findings demonstrate that lozenge and spray formulations of flurbiprofen can penetrate throughout the layers of cadaveric human pharynx tissue in an ex vivo model, as visualized by microautoradiography.Keywords: flurbiprofen, Franz diffusion cell, microautoradiography, pharynx